2018
DOI: 10.15406/mojwh.2018.07.00176
|View full text |Cite
|
Sign up to set email alerts
|

The effect of infertility upon quality of life and self-esteem

Abstract: Aim:In this study we aimed to determine the effect of infertility upon the quality of life and self-esteem and by this means guide nurses in taking care of and giving counseling to the infertile individuals. Method: 150 individuals (100 females and 50 males) entered into the study, who came to be treated in the in vitro fertilization or IVF unit in the Medical Faculty Hospital at Bezmialem Foundation University between 26th July, 2016 and 26th January, 2017 and matched the research criteria. We collected the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Similar to previous surveys in Northeast and Southeast China, we found that the self-esteem of infertile couples undergoing IVF-ET is at the middle level ( Cui C. et al, 2021 ; Wang et al, 2022 ). In contrast, infertile couples in Turkey ( Çavdar and Coşkun, 2018 ), Athens ( Ruth and Akintayo, 2021 ), and Egypt ( Zayed and El-Hadidy, 2020 ) had low self-esteem and those in western countries such as American, had a higher self-esteem than the general population ( Cizmeli et al, 2013 ). These differences could be the result of socioeconomic and cultural heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous surveys in Northeast and Southeast China, we found that the self-esteem of infertile couples undergoing IVF-ET is at the middle level ( Cui C. et al, 2021 ; Wang et al, 2022 ). In contrast, infertile couples in Turkey ( Çavdar and Coşkun, 2018 ), Athens ( Ruth and Akintayo, 2021 ), and Egypt ( Zayed and El-Hadidy, 2020 ) had low self-esteem and those in western countries such as American, had a higher self-esteem than the general population ( Cizmeli et al, 2013 ). These differences could be the result of socioeconomic and cultural heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Family relationships, psychosocial stress, and physical pain caused by their infertility and treatment are the risk factors that affect the self-esteem of couples undergoing IVF-ET ( Zurlo et al, 2020 ; Jing et al, 2021 ; Liu et al, 2021 ; Zhang et al, 2022 ). Many studies in the past have shown that one of the most prominent problems in the infertile population is stigma, which leads to varying degrees of reduced self-esteem ( Cizmeli et al, 2013 ; Çavdar and Coşkun, 2018 ; Ruth and Akintayo, 2021 ; Cui C. et al, 2021 ). The level of self-esteem has an impact on coping strategies.…”
Section: Introductionmentioning
confidence: 99%